2019
DOI: 10.1111/ajag.12627
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Australian Ageing Semantic Differential, a new instrument for measuring Australian medical student attitudes towards older people

Abstract: Objective This study outlines development of an instrument for measuring attitudes of medical students towards older people, the Australian Ageing Semantic Differential (AASD). Methods Words for AASD scales were derived from the reflections of 151 third year medical students attending two Australian medical schools. A pilot study of the AASD was then undertaken with third year students at another medical school to confirm usability and reliability of the instrument. After slight modification, a larger study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This study has provided robust evidence that the AASD as a measure of medical student attitudes towards older people is generalisable across both undergraduate and graduate medical programmes in Australia, and has performed with very good internal consistency in studies to date. As was demonstrated previously by the AASD developmental study findings from student surveys across three NSW medical schools (mean AASD score 73.2/114 and Cronbach's alpha=0.86), 28 this study of medical students outside NSW has again demonstrated positive Australian medical student attitudes towards older people (mean AASD score 72.8/114 and Cronbach's alpha=0.84). Independent t-testing confirms no significant difference in mean AASD scores of students surveyed outside NSW when compared with their NSW counterparts.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This study has provided robust evidence that the AASD as a measure of medical student attitudes towards older people is generalisable across both undergraduate and graduate medical programmes in Australia, and has performed with very good internal consistency in studies to date. As was demonstrated previously by the AASD developmental study findings from student surveys across three NSW medical schools (mean AASD score 73.2/114 and Cronbach's alpha=0.86), 28 this study of medical students outside NSW has again demonstrated positive Australian medical student attitudes towards older people (mean AASD score 72.8/114 and Cronbach's alpha=0.84). Independent t-testing confirms no significant difference in mean AASD scores of students surveyed outside NSW when compared with their NSW counterparts.…”
Section: Discussionsupporting
confidence: 85%
“…Pilot study of the prototype survey instrument was performed with third-year medical students attending the University of New South Wales medical school in late 2016, demonstrating internal reliability and usability for this instrument. 27 A recently published paper describes further development of the AASD from data obtained from surveying students in three NSW medical schools. 28 The AASD consists of 19 pairs of opposite adjectives, and can be viewed in figure 1.…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations